The Effects of Interest and Inflation Rates on Consumption Expenditure: Application of Consumer Spending Model - Manasseh, Charles O.; Abada, Felicia C.; Ogbuabor, Jonathan E.; Onwumere, Josaphat U. J.; Urama, Chinasa E.; Okoro, Okoro E. (International Journal of Economics and Financial Issues, 2018)
Using modified consumer spending model and data that span the period of 1981-2011, the study examines the effects of interest and inflation rates (proxy - consumer price index) on Consumer Spending. The study extended its investigation into the causal relationship between consumer spending (proxy; private consumption expenditure), interest and inflation rates using granger causality Wald test, so as to ascertain if consumer spending can be use to predict future interest and inflation rates in the economy. The findings suggest that all explanatory variables account for approximately 93.38 percent variation in consumer spending, indicating interest and inflation rates and other control variables such as per capita income (PCI), indirect tax (INDTAX) and savings (SAV) as important determinants of private consumption expenditure in Nigeria. The results on the granger causality indicated that future interest and inflation rates cannot be predicted using private consumption expenditure. Therefore, based on these findings, we recommend expansionary fiscal and monetary policies to influence the level of aggregate demand in the economy. Keywords: Consumer Spending, Inflation Rate, Interest Rate, Granger Causality. JEL Classifications: D11, D12